PEMBERDAYAAN KAWASAN PESISIR UTARA BANTEN MELALUI KELOMPOK USAHA BERSAMA BERBASIS KEARIFAN LOKAL - Wigati, Restu; Kulsum, Kulsum; Bethary, Rindu Twidi (Jurnal Pengabdian Dinamika, 2018)
One of the constraints of coastal areas is the difficulty of providing clean water caused by the entry of sea water into the ground water. The difficulty in obtaining clean water makes Domas Village community to find an alternative, one through the use of the rainwater. In addition to clean water problems, poverty is also one of the complicated problems in Pontang Sub-district. The Real Work Experience Community Empowerment Learning (KKN-PPM) conducted by the team of Field Supervisors and Students of the University of Sultan Ageng Tirtayasa (UNTIRTA) by creating and applying a simple water purification equipment design to meet the needs of clean water, improve and develop the business groups of society through its typical food is "bontot ikan". Target and achievements of KKN-PPM activities that have been implemented in Domas Village, Pontang District, Serang Regency with students and society as supports of the community empowerment process include: the increasing of public knowledge about environmental issues, healthy lifestyles through clean water and sanitation, the increasing people's skills on the application of appropriate technology through water purification techniques, the increasing of society skill in the management of small industry, the increasing of society's knowledge in the development of processed marine based food products, the formation of joint business group (KUBE) of Domas Village, and has socialized the declaration of community development as a form of reciprocity from the villagers of Domas Village through KKN-PPM activities.